Prediction of 5‐year overall survival of diffuse large B‐cell lymphoma on the pola‐R‐CHP regimen based on 2‐year event‐free survival and progression‐free survival - Wan‐Ru Zhang; Xin Liu; Qiu‐Zi Zhong; Tao Wu; Yong Yang; Bo Chen; Hao Jing; Yuan Tang; Jing Jin; Yue‐Ping Liu; Yong‐Wen Song; Hui Fang; et al. (Cancer Medicine, 2024)
Abstract This study aimed to predict the 5‐year overall survival (OS) benefit of pola‐R‐CHP versus R‐CHOP in the POLARIX trial based on the 2‐year event‐free survival (EFS) and progression‐free survival (PFS) rates in diffuse large B‐cell lymphoma (DLBCL). We identified randomized controlled trials (RCT) published before 31 May 2023. The correlation between the logarithmic (log) hazard ratio (HR) for EFS (HREFS) or PFS (HRPFS) and the HR for OS (HROS) was estimated at the trial‐level. Correlation analysis was performed between 2‐year PFS or EFS and 5‐year OS rates at the treatment arm‐level. Linear regression models were used to calculate the 5‐year OS of pola‐R‐CHP and R‐CHOP. In the included 20 RCTs, a linear correlation between HREFS (r = 0.765) or HRPFS (r = 0.534) and HROS was observed at the trial‐ level. Two‐year EFS (r = 0.918) or 2‐year PFS (r = 0.865) correlated linearly with 5‐year OS. Linear regression analysis between 2‐year EFS/PFS and 5‐year OS gave estimated 5‐year OS rates between pola‐R‐CHP and R‐CHOP of 6.4% and 6.3%, respectively. Two‐year EFS and PFS are feasible early endpoints in patients with DLBCL treated primarily with immunochemotherapy. The pola‐R‐CHP regimen is expected to improve 5‐year OS.